2010
DOI: 10.1073/pnas.1006285107
|View full text |Cite
|
Sign up to set email alerts
|

Prior knowledge of illumination for 3D perception in the human brain

Abstract: In perceiving 3D shape from ambiguous shading patterns, humans use the prior knowledge that the light is located above their head and slightly to the left. Although this observation has fascinated scientists and artists for a long time, the neural basis of this "light from above left" preference for the interpretation of 3D shape remains largely unexplored. Combining behavioral and functional MRI measurements coupled with multivoxel pattern analysis, we show that activations in early visual areas predict best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 39 publications
5
44
0
Order By: Relevance
“…Activity in this area may reflect deployment of attention to internal mnemonic representations, as stated in the attention to memory hypothesis (AtoM; Wagner et al, 2005). Accordingly, the SMG usually shows decreased BOLD fMRI activity for less familiar information (Wagner et al, 2005;Ciaramelli et al, 2008), potentially corresponding to unusual illumination conditions here. To link these fMRI findings to our MEG results, we draw on the well established positive correlation of the BOLD fMRI signal with GBA in MEG (Brookes et al, 2005).…”
Section: Gba Additionally Reflects Attentional Effectsmentioning
confidence: 83%
See 1 more Smart Citation
“…Activity in this area may reflect deployment of attention to internal mnemonic representations, as stated in the attention to memory hypothesis (AtoM; Wagner et al, 2005). Accordingly, the SMG usually shows decreased BOLD fMRI activity for less familiar information (Wagner et al, 2005;Ciaramelli et al, 2008), potentially corresponding to unusual illumination conditions here. To link these fMRI findings to our MEG results, we draw on the well established positive correlation of the BOLD fMRI signal with GBA in MEG (Brookes et al, 2005).…”
Section: Gba Additionally Reflects Attentional Effectsmentioning
confidence: 83%
“…PEs are therefore likely to arise in areas involved in the processing 3D shape from shading cues, such as the MFC (Taira et al, 2001). Additionally, SFS may be used to keep shading cues in working memory (Courtney et al, 1998) and ACG may support error detection (Botvinick et al, 2004). Thus, we interpret this illumination effect as a PE signal for the unexpected illumination.…”
Section: Cortical Source Power Changes In High-frequency Gba Reflect Pesmentioning
confidence: 99%
“…Several earlier studies examined the cortical responses to shading in humans (Georgieva et al, 2008;Gerardin et al, 2010;Humphrey et al, 1997;Kourtzi et al, 2003;Moore and Engel, 2001;Taira et al, 2001) and macaques (Arcizet et al, 2009;Hanazawa and Komatsu, 2001;Nelissen et al, 2009), mainly in relation to 3D shape perception from shading. Some of the human fMRI studies reported activation in the higher visual areas, such as the LOC (Kourtzi et al, 2003;Moore and Engel, 2001) and right intraparietal area (Taira et al, 2001), while others also reported response modulation in the early visual areas (Humphrey et al, 1997;Taira et al, 2001), which is consistent with our finding that the early areas responded to surface cues.…”
Section: Discussionmentioning
confidence: 99%
“…This is because the convention is not necessarily determined by geography or topography, rather it is fundamentally linked to how the HVS functions. Several studies in perceptual psychology have attempted to measure the overhead illumination bias and observed that, if no other cues are present to indicate the illumination position, the HVS assumes the light to shine not exactly from overhead but from slightly above left, referred to as light-from-aboveleft preference or left bias (Gerardin, Kourtzi, and Mamassian 2010;Mamassian and Goutcher 2001;Sun and Perona 1998). The link between these observations in the perceptual psychology domain and the cartographic convention is not explicitly established in the literature until this point.…”
Section: Cartographic Convention For Shaded Relief Maps and Perceptuamentioning
confidence: 99%